Effectiveness over time of varicella vaccine. - Vázquez, Marietta; LaRussa, Philip S; Gershon, Anne A; Niccolai, Linda M; Muehlenbein, Catherine E; Steinberg, Sharon P; Shapiro, Eugene D (JAMA : the journal of the American Medical Association, 2004)
Reports of outbreaks of varicella in highly immunized groups have increased concern about the effectiveness of varicella vaccine.
Keywords: Adolescent; Age Factors; Case-Control Studies; Chickenpox; Chickenpox Vaccine; Child; Child, Preschool; DNA, Viral; Female; Herpesvirus 3, Human; Humans; Immunity, Active; Immunization Schedule; Infant; Male; Polymerase Chain Reaction; Time Factors; Vaccination